Factors of competitiveness and strategies to improve exports of chicken products in Indonesia - Wibowo, A. H.; Muzayyanah, M. A. U.; Guntoro, B. (Journal of the Indonesian Tropical Animal Agriculture, 2025)
The livestock subsector contributes around sixty percent of the gross domestic product (GDP) of the agricultural sector, and poultry products approximately 80.77% of total national livestock production. Although Indonesia's poultry industry shows great potential, exports of Indonesian broiler products still face various obstacles, for instance geographical distance between countries, exchange rates, Covid-19 pandemic and implementation of Free Trade Agreements (FTA). This study aimed to analyze the determinant factors of the export competitiveness of Indonesian chicken products in the international market with a descriptive quantitative method using Likert-scale questions . This study involved the entire population of 45 individuals, consisting of poultry companies engaged in export activities and relevant government institutions. The Gravity Model approach was employed to examine economic and geographical factors, while the Porter Diamond framework was used to assess the determinants of the industry’s competitive advantage. The results showed that geographical distance (-0.09), exporter GDP (0.27), and importer GDP (0.04) affected to export performance. The most influential factors on Indonesia’s chicken products export competitiveness were firm strategy, structure, and rivalry—particularly product adaptation to target markets (4.61)—and government support through export procedure simplification (4.59). Furthermore, related and supporting industries were found to have a strong correlation with competitiveness. The strengths, weaknesses, opportuni-ties, and threats (SWOT)  analysis resulted diversification strategies in both products and markets, as well as the integration of digital technology in production and distribution become strategic steps to enhance export competitiveness.